The Role and Therapeutic Perspectives of Sirtuin 3 in Cancer Metabolism Reprogramming, Metastasis, and Chemoresistance - Zhao, QingYi; Zhou, Jing; Li, Feng; Guo, Sen; Zhang, Liang; Li, Jing; Qi, Qin; Shi, Yin (Frontiers in Oncology, 2022)
Sirtuin 3 (SIRT3), the nicotinamide adenine dinucleotide (NAD+)-dependent deacetylase, acts as a metabolic modulator mainly located in mitochondria via regulating the process of the relevant biochemical processes by targeting crucial mediators. Recently, owing to its dual role in cancer, SIRT3 has attracted extensive attention. Cancer cells have different metabolic patterns from normal cells, and SIRT3-mediated metabolism reprogramming could be critical in the cancer context, which is closely related to the mechanism of metabolism reprogramming, metastasis, and chemoresistance in tumor cells. Therefore, it is crucial to elucidate the relevant pathological mechanisms and take appropriate countermeasures for the progression of clinical strategies to inhibit the development of cancer. In this review, existing available data on the regulation of cancer metabolism reprogramming, metastasis, and chemoresistance progression of SIRT3 are detailed, as well as the status quo of SIRT3 small molecule modulators is updated in the application of cancer therapy, aiming to highlight strategies directly targeting SIRT3-mediated tumor-suppressing and tumor-promoting, and provide new approaches for therapy application. Furthermore, we offer an effective evidence-based basis for the evolvement of potential personalized therapy management strategies for SIRT3 in cancer settings.